Angiogenesis in brain contusion - Mariusz Kobek; Rafał Skowronek; Zbigniew Jankowski; Artur Pałasz (Archives of Forensic Medicine and Criminology, 2015)
In the forensic medicine, objective and, if possible, the most accurate determination of the age – the time of the brain contusion, has practical significance. In our previous work, we discussed the importance of the neuron cytoskeleton proteins – neurofilaments, in this area. The purpose of this paper is to present the possibilities of using the phenomenon of angiogenesis in the brain contusions, to determine its age, on the basis of previous studies in animal models and in human biological material. The current review of the literature showed no conclusive data that would allow use morphological changes in angiogenesis to determine the age of the brain contusion in forensic medical practice. For these reasons, it is reasonable to take a broader research on the human material.